Peran Guru BK dalam Pembinaan Kedisiplinan Siswa SMAK Giovanni Kupang Melalui Layanan Bimbingan Kelompok - Malelak, Grace Darlene; Sembiring, Kristinus (FKIP Universitas Islam Jember, 2025)
This study aims to describe the role of Guidance and Counseling (BK) teachers in fostering student discipline at SMA Katolik Giovanni Kupang through group guidance services. The research used a descriptive qualitative approach, collecting data through interviews and observations with the BK teacher and students who had records of tardiness. The findings reveal that the BK teacher plays a strategic role as a facilitator, mediator, and motivator in fostering students’ disciplinary awareness. Group guidance services proved effective in improving students’responsibility and time management, as evidenced by the decrease in tardiness frequency after the sessions. The causes of tardiness include internal factors such as late-night habits and low motivation, and external factors such as transportation issues and limited parental support. The main obstacles were the lack of parental involvement and time constraints for counseling activities. This study concludes that discipline formation is more effectively achieved through humanistic and collaborative educational approaches rather than punitive measures.